If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(1-x)/11=6
We move all terms to the left:
(1-x)/11-(6)=0
We add all the numbers together, and all the variables
(-1x+1)/11-6=0
We multiply all the terms by the denominator
(-1x+1)-6*11=0
We add all the numbers together, and all the variables
(-1x+1)-66=0
We get rid of parentheses
-1x+1-66=0
We add all the numbers together, and all the variables
-1x-65=0
We move all terms containing x to the left, all other terms to the right
-x=65
x=65/-1
x=-65
| a/2 + 2a/5 = 18 | | 2^2x+2^x+1=80 | | (9-x)/12=-12 | | a + 2a = 182 5 | | 3(7-x)=1 | | (x-7)/7+6=1 | | 8x-17=5x+9 | | 2x-4=10x-4 | | (x+1)/3+2=7 | | 10y-9=6y-12 | | 3x15=8x+25 | | (8x+1)/7=-1 | | 7y-12=6y-8 | | (4x-2)/5=10 | | 3x-1=8x-`1 | | 6-(x)/11=7 | | (y-4)-(y-5)=4y | | 3-(x)/12=7 | | b/5+1/9=16 | | 5-(x)/12=8 | | 4x+6=-6+2x+22 | | 1=0.2x-0.9x=20 | | 4.9+10m=8.63 | | 11-(x)/6=-11 | | 3*2^x-5*2^x+1+5*2^x+3-2^x+5=2 | | -6+1=2(x+3)+4x | | 7(2x-3=63 | | 4=-3/x+3 | | 2(-3+5)-8=x+17 | | 2-(-3+5)-8=c+17 | | x-x/5=48 | | 4.1+10m=7.32 |